2005
DOI: 10.1677/jme.1.01770
|View full text |Cite
|
Sign up to set email alerts
|

Expression of recombinant membrane-bound type I iodothyronine deiodinase in yeast

Abstract: The bioactivity of thyroid hormone is determined to a large extent by the monodeiodination of the prohormone thyroxine (T4) by the hepatic selenoenzyme type I iodothyronine deiodinase (D1), i.e. by outer ring deiodination (ORD) to the active hormone triiodothyronine (T3) or by inner ring deiodination (IRD) to the inactive metabolite reverse T3 (rT3). Since D1 is a membrane-bound protein with an N-terminal membrane-spanning domain, the enzyme is very difficult to purify in an active state. This study was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
1
7
0
1
Order By: Relevance
“…The biophysical and structural characterization of deiodinases is severely aggravated by the fact that they are integral transmembrane proteins and selenoenzymes. The mechanism of Sec incorporation differs between eukaryotes and bacteria, hampering the expression of fully active, recombinant mammalian deiodinase protein in the widely used, efficient prokaryotic expression systems (Kuiper et al 2005b). Expression of a Cys-mutant Dio1 in yeast yielded an active but heterogenous protein that did not allow structural studies (Kuiper et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biophysical and structural characterization of deiodinases is severely aggravated by the fact that they are integral transmembrane proteins and selenoenzymes. The mechanism of Sec incorporation differs between eukaryotes and bacteria, hampering the expression of fully active, recombinant mammalian deiodinase protein in the widely used, efficient prokaryotic expression systems (Kuiper et al 2005b). Expression of a Cys-mutant Dio1 in yeast yielded an active but heterogenous protein that did not allow structural studies (Kuiper et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of Sec incorporation differs between eukaryotes and bacteria, hampering the expression of fully active, recombinant mammalian deiodinase protein in the widely used, efficient prokaryotic expression systems (Kuiper et al 2005b). Expression of a Cys-mutant Dio1 in yeast yielded an active but heterogenous protein that did not allow structural studies (Kuiper et al 2005b). In the absence of experimental structural information, modeling of human deiodinases suggested that a Dio-specific insertion in the Trx-like sequence forms a glycoside hydrolase like insertion in the basic Trx fold (Callebaut et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For ID, excision of its predicted transmembrane anchor still did not yield soluble protein (44). For IYD, limited proteolysis by trypsin did generate a soluble and active protein, presumably by hydrolysis of a single terminal peptide anchor.…”
Section: Discussionmentioning
confidence: 96%
“…Enzyme Solubilization, Isolation, and Identification-Purification and detailed mechanistic study of both IYD and ID have been hindered by their association with cell membranes (36,44). For ID, excision of its predicted transmembrane anchor still did not yield soluble protein (44).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture remains the most common source of ID 22,23 despite recent success in heterologous expression of ID in yeast. 24 Attempts to generate a soluble form of ID have not yet been successful. Deletion of its N-terminal membrane anchor yielded only inactive protein.…”
Section: Introductionmentioning
confidence: 99%